The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3109/0284186x.2013.812795
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of metabolic metrics extracted from baseline positron emission tomography images in non-small cell lung cancer

Abstract: Background Maximum, mean and peak SUV of primary tumor at baseline FDG-PET scans, have often been found predictive for overall survival in non-small cell lung cancer (NSCLC) patients. In this study we further investigated the prognostic power of advanced metabolic metrics derived from Intensity-Volume Histograms (IVH) extracted from PET imaging. Methods A cohort of 220 NSCLC patients (mean age, 66.6 years; 149 men, 71 women), stages I-IIIB, treated with radiotherapy with curative intent were included (NCT005… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 21 publications
0
40
0
Order By: Relevance
“…Radiomics, an advanced analysis platform, extracts features from medical images by using mathematical algorithms based on tumor intensity, gray-level intensities, and texture [6][7][8][9]15,[18][19][20][21]. We have previously identified radiomics-based signatures that are prognostic and associated with proliferation-related gene signatures [7].…”
Section: Discussionmentioning
confidence: 98%
“…Radiomics, an advanced analysis platform, extracts features from medical images by using mathematical algorithms based on tumor intensity, gray-level intensities, and texture [6][7][8][9]15,[18][19][20][21]. We have previously identified radiomics-based signatures that are prognostic and associated with proliferation-related gene signatures [7].…”
Section: Discussionmentioning
confidence: 98%
“…Compared with Adk, Sqc is characterized by higher SUV max , AUC-IVH, energy GLMC , entropy GLCM , sum entropy, difference entropy, and inverse different moment and by lower homogeneity GLCM , sum of squares, angular second moment, ratio of non-zero Gr , and difference variance 6062 . Prognostic and predictive role Heterogeneity (i.e., AUC-CSH) can predict recurrence in pN0 Adk patients who have undergone curative surgery but not in Sqk patients (high heterogeneity is associated with a shorter DFS) 61 .Best prognostic value for overall survival is found for relative portions of the tumor above higher uptakes defined as SUV max  > 80% (i.e., V 80 ) in patients who received radiation therapy (sequential chemoradiation, concurrent chemoradiation, or only radiation). The higher the portion above higher uptake (V 80 ), the better the prognosis 29, 80 .Heterogeneity (i.e., low AUC-CSH) identifies patients with inoperable stage III NSCLC with poor PFS 75 .High SUV max , large MTV, and high heterogeneity (i.e., high entropy GLCM , high asphericity, homogeneity GLCM , and high dissimilarity, size-zone variability, and low zone percentage) are associated with poorer OS and RFS in stage I–III NSCLC 35, 73, 74, 83 .Tumor heterogeneity (i.e., entropy GLCM ) is associated with response to radiation therapy in NSCLC (DSS is lower for patients with high entropy GLCM ) 79 .Lesions in responders (complete or partial response) to chemoradiotherapy are characterized by lower coarseness, contrast NGTDM , and busyness than non-responders (stable or progressive disease). High coarseness values are associated with an increased risk of progression (increased risk of death), whereas high contrast NGTDM and busyness values are associated with a lower risk of progression (PFS and LPFS) 14 .Large primary tumors with low SumAverage (i.e., more heterogeneous) have a poor prognosis following chemoradiotherapy 76 .Lesions in responders to erlotinib are characterized by lower heterogeneity than those in non-responders.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the FDG PET/CT scanners used in the study and clinical variables in the modeling and validation cohorts mimic real world situations, suggesting that the MTVwb risk stratification system developed and validated in this study may be generalizable to other centers. There are other reasons to expect that the MTVwb risk stratification system can be used in other centers and be practical in clinical use including: 1) measurement of MTVwb is practical with commercially available software, and semi-automatic tumor segmentation is as accurate as manual segmentation for primary NSCLC tumors [25]; 2) MTVwb estimates are relatively insensitive to different FDG PET/CT scanners and image-reconstruction algorithms [26]; 3) a number of studies have demonstrated consistently significant correlation between survival and MTVwb in NSCLC, in different parts of the world, and with different FDG PET/CT scanners[211, 13, 14, 2731], 4) the variability of metabolic tumor volume in NSCLC primary tumors is less than that of SUV for NSCLC primary tumor in PET scans of 1-hour vs. 2-hour FDG uptake time [32]; and 5) MTVwb measurements are relatively immune to inter-observer variability[2, 5]. …”
Section: Discussionmentioning
confidence: 99%